Analytical Model for Electronic Transport in Semiconductor Thin Films (2013)
Polycrystalline semiconductors are materials who often exhibit unusual electrical properties. In the model we assume that the crystals are composed of semiconductor material, the grain itself, which is surrounded by highly disordered and resistive materials, the grain boundary. The grain boundary disturbs the structural regularity of the crystal giving rise to localized electronic states within the energy gap. The existence of these states promotes the charge trapping at the grain boundaries and the bending of the energy bands. This bending is characterized by a potential barrier and a space charge zone which control the electron transport through the grain boundary. The model uses the diusion and drift carriers theories, and thermoionic emission, and the quantum tunneling of carriers through the potential barrier was also taken into consideration. Since the structure of the thin lms of molybdenum trioxide (MoO3) obtained through spray pyrolysis is granular and nanosize, the model described the behavior of the current-voltage characteristic (I-V) of the films.